Bollywood Banned and the Electrifying Palmasutra - Casey, Conerly (Asian Video Cultures: In the Penumbra of the Global, 2017)
The contributors to this volume theorize Asian video cultures in the context of social movements, market economies, and local popular cultures to complicate notions of the Asian experience of global media. Whether discussing video platforms in Japan and Indonesia, K-pop reception videos, amateur music videos circulated via microSD cards in India, or the censorship of Bollywood films in Nigeria, the essays trace the myriad ways Asian video reshapes media politics and aesthetic practices. While many influential commentators overlook, denounce, and trivialize Asian video, the contributors here show how it belongs to the shifting core of contemporary global media, thereby moving conversations about Asian media beyond static East-West imaginaries, residual Cold War mentalities, triumphalist declarations about resurgent Asias, and budding jingoisms. In so doing, they write Asia's vibrant media practices into the mainstream of global media and cultural theories while challenging and complicating hegemonic ideas about the global as well as digital media.<br

Companion to Psychological Anthropology: Modernity and Psychocultural Change - Casey, Conerly; Edgerton, Robert B. (lackwell Publishers, 2005)

Eco-intimacy and spirit exorcism in the Nigerian Sahel - Casey, Conerly (Senses and Society, 2021)
A fervent politics of the senses sparked off in northern Nigeria, when, in 1995, more than 600 Muslim secondary school girls became possessed by spirits, with the new sign of “dancing like they do in Indian film.” Spirit possession in this Bollywood form spread across northern states, co-evolving with a meningitis epidemic as it swept through the desert to kill thousands. This article traces emergent eco-intimacies and the resonant politics of the senses as Bori and Qur’anic scholar-healers, or malams, linked these events, via assertions of ontological power, in the sensory geographic and affective-material movements of humans, spirits and pathogens. Malams reprimanded followers of Bori for calling spirits with music and dance, thus eroding the geographic and bodily boundaries between humans and spirits. They converted humans and spirits to their forms of orthodoxy before expelling spirits from their human hosts. The sensory politics of boundary monitoring and maintenance that emerged underpinned the 2000 implementation of sharia criminal codes across northern states. But, the affective senses of contamination and care did not align with any singular spiritual-political position, eliciting ongoing debates over appropriate spirit-human contact, and double binds in the sensory politics of medicine and state.
Created from Fastlane, Scopus look-up
Keywords: Bori; eco-intimacy; exorcism; Islam; Nigeria; Senses; spirit possession

"Marginal Muslims": Politics and the perceptual bounds of Islamic authenticity in northern Nigeria - Casey, Conerly C. (Africa Today, 2008)
In 1999 and 2000, twelve states in northern Nigeria declared Islamic law (Shari'ah) the state criminal law for all Muslims, redefining the boundaries of identity, civility, and criminality. In the city of Kano, the implementation of Shari'ah criminal codes appealed to Muslims from all sectors of society, as democratic alternative to, and strong critique of, colonialism and the elitism and corruption of federal and state politicians. Urban ward gang members ('yan daba) agitated alongside other Muslim youths for the implementation of Shari'ah codes, yet with others deemed "marginal Muslims," became the immediate objects of preaching and surveillance by Hisbah (Shari'ah enforcers). Perceptual experiences in everyday life - whether one wore the beard of Muslim orthodoxy, or the baggy jeans and chains of Los Angeles rappers, or prayed at the tombs of Sufi saints - began to redefine and frame identity in terms of ethnic, Islamic "authenticity," morality, and neighborhood and state security. In this article, I describe the changing relations of Hisbah and 'yan daba during the 2000 implementation of Shari'ah codes in Kano, providing an analysis of the impact of the implementation itself on nonreformist residents. I show that reformist Hisbah vigilantly scrutinized Muslims living in ethnically plural spaces, Muslim ethnic minorities, and people who, by virtue of their region of origin, religion, or ethnicity, were deemed to be "marginal Muslims" or polytheists, and thus, "out of place." Reformist Hisbah considered Muslim 'yan daba, 'yan Bori (followers of Bori), nonreformist Sufis (with pro-Shari'ah Sufi critics of Hisbah), and non-Hausa Muslims, particularly Muslim Yoruba, to be political-spiritual saboteurs who dis-allowed the reenchantment of orthodoxy and its ability to function as Islamic political unity and collective memory. For 'yan daba and Hisbah, Islamic state-building became a work of ethnic, religious, and regional conflation, which through unlawful displays of masculine power conflicted with the political aspirations of moderate Muslim Hausa, and superseded personal and non-Muslim Hausa expressions of Islamic authenticity, morality, and security.
Created from Fastlane, Scopus look-up

Mediated Hostility - Casey, Conerly (Genocide: Truth, Memory, and Representation, 2009)

Mediated hostility, generation and victimhood in northern Nigeria - Casey, Conerly (Regional and Ethnic Conflicts: Perspectives from the Front Lines, 2008)

Mediating justice: Youth, media and ‘affective justice’ in the politics of northern Nigeria. - Casey, Conerly (Democracy and Prebendalism in Nigeria> Critical Interpretations, 2013)
Recent protests across North Africa and the Middle East testify to public outrage at the failure of postcolonial states to produce “justice” in their governance structures. Attempts at the federal level in Nigeria to enact justice and institute accountability have led to changes to the Independence Constitution of 1960 in 1963, 1979, 1989, and 1999, to the deregulation of capital in the 1990s and the primacy of the market, and to demilitarization, in 1999, coinciding with democratic elections. Inflation in the 1990s, and unprecedented levels of poverty and insecurity that accompanied these efforts, mediated and refracted in political allegations of blame, galvanized Christian and Muslim reformist networks, as well as groups of armed youths who use violence to control the means of coercion. These armed groups gain advantage in conflicts over state and national sovereignty, the control of public space, and the appropriation and distribution of resources, their views and actions defining imaginings of Nigeria in national, transnational, and social media (Abbink and Kessel 2005; Adebanwi 2005, 2008; Akinyele 2001; Baker 2002; Casey 2007, 2008, 2009; Comaroff and Comaroff 2006; Mbembe 2001; Nolte 2004; Obadare 2006; Pratten 2007; Smith 2004, 2007). As the implementation of Shari’ah criminal codes in northern Nigeria, and regime change in the context of the Arab Spring confirm, young people have the capacity to reform and enact diasporic, micronational, national, and transnational forms of “justice,” exerting extraordinary public pressure for governmental chang

Memories of violence in spiritual renewal - Casey, Conerly (Sikh Formations: Religion, Culture, Theory, 2020)
Spectres of the 1984 violence against Sikhs and Ahmadis in the Indian and Pakistan border areas of Punjab are fascinating mediums for Michael Nijhawan’s new book, The Precarious Diasporas of Sikh and Ahmadiyya Generations: Violence, Memory and Agency. Though violence against Sikhs and Ahmadis had taken place before, Nijhawan suggests the scale of violence in 1984 altered social imaginaries and biographies of migration, which youths inherit and de-inherit in today’s precarious diasporas. Beyond ‘postmemory,’ this essay considers memories of violence in mediated messianic spatiotemporalities, ethical forms of agency, and spiritual renewal, which emerge so strongly in Nijhawan's research.
Created from Fastlane, Scopus look-up

Perceptions about Risk for HIV/AIDS among Adolescents in Juvenile Detention - Anderson, Nancy Lois Ruth; Nyamathi, Adeline; McAvoy, Julie A; Casey, Conerly; et al. (Western Journal of Nursing Research, 2001)
Although progress has been made toward reducing risk-taking behavior among teens, adolescents confined in juvenile detention facilities and youths living in inner cities remain vulnerable. Reaching these populations with appropriate risk-reduction strategies continues to challenge health providers and educators. Crucial first steps in the design of relevant programs involve discovering how at-risk teens perceive risk and which risks and dangers within their communities occupy their attention. Participants in this study did not identify HIV/AIDS as a primary concern; instead, they described the dangers and risks they encountered in their home neighborhoods. Based on these findings, this discussion addresses the implications for the development of health education programs to empower teens for responsible behavior after release from detention.<br

Remembering and ill health in postinvasion Kuwait: Topographies, collaborations, mediations - Casey, Conerly (Cambridge University Press, 2014)
Awakened by the pummeling blasts of nearby explosions, Dalia was unable to fall back asleep. Trembling, she crawled under her bed to hide, then ran to find her mother in the living room of their family’s home. Dalia knew immediately from her mother’s whispers and worried expression that Iraqi soldiers had invaded Kuwait. Dalia’s family, unlike many others who fled to neighboring or to European countries after the August 2, 1990, Iraqi invasion, remained in Kuwait during the seven-month occupation, covering their windows with blankets and sticky tape, little protection from the shattering glass of mortar explosions and gunfire. They talked their way past heavily armed Iraqi soldiers to search for food and water and, later, lived in sooty darkness, breathing in the residues of burning oil fires and other war contaminants.The 1990 Iraqi invasion and occupation of Kuwait led to highly mediated, emotionally charged ideas, images, and sounds of war, affective mediations of violence that continue to circulate. Less accessible to media audiences is the Harvard Schoolof Public Health (HSPH, 2005) finding that Kuwaitis, aged fifty years or older, who had remained in Kuwait for all or part of the occupation, were at 20–30 percent greater risk of mortality than those who fled the country. John Evans (2008; HSPH, 2005), director of theHarvard School of Public Health assessment of postinvasion health, suggested that smoke frommore than seven hundred oil fires burning from January to November of 1991 contributed to these higher mortality rates, though not in ways sufficient to cause the observed increases. After screening for “other contaminants – such as volatile organic compounds, polycyclic aromatic hydrocarbons and metals from the oil lakes and marine oil spills; and depleted uranium,” the HSPH (2005) team concluded that “exposures to these compounds were unlikely to lead to appreciable risks to public health.” The HSPH team, collaborating with Professor Jaafar Behbehani (Kuwait University Faculty of Medicine) and his colleagues at Kuwait’s Al-Riggae Specialized Centre (Hammadi, 1994), suggested instead that a combination of oil smoke and PTSD would explain the higher prevalence of mortality inthe fourteen years since independence (HSPH, 2005).
Created from Fastlane, Scopus look-up

Remembering Genocide: Hypocrisy and the Violence of Local/Global “Justice” in Northern Nigeria - Casey, Conerly (Transitional Justice: Global Mechanisms and Local Realities after Genocide and Mass Violence, 2010)

Sensory Politics and War: Affective Anchoring and Vitality in Nigeria and Kuwait - Casey, Conerly (POLITICAL SENTIMENTS AND SOCIAL MOVEMENTS: THE PERSON IN POLITICS AND CULTURE, 2018)
Created from Fastlane, WoS look-up

“States of emergency”: Armed youths and mediations of Islam in northern Nigeria - Casey, Conerly (Journal of International and Global Studies, 2014)

Studies in Cultural Sociology - Casey, Conerly; Salisu, Abdullahi; Zango, Ismaila (Espee Printing, 2008)

The art of suffering: Postcolonial (Mis)Apprehensions of Nigerian art - Casey, Conerly (Suffering, Art and Aesthetics, 2014)
(Mis)apprehensions of African arts, and their relegation to distant temporal, spatial, and relational realms, are part of violent structures of power that continue to diminish our understanding of others. European and American representations of African arts and aesthetics, embedded in what James Clifford (1988, 225) refers to as the “art-culture” system, tend to devalue them as “primitive,” signs of stagnant, traditional, and unchanging culture, or to value “authentic” forms, typically precolonial art, assumed to hold ritual power.1 With Europeans and Americans, the primary buyers of “authentic” African art, this double bind leaves contemporary African artists unable to sell their work in global art markets, their creativity sidelined to “fake” antiques, or to “copy” Western music, in mimetic processes that entangle African and European artists and consumers. Within the past two decades, however, the global marketing of African art and aesthetics appears to have morphed; European and American consumers continue to assume transcultural, cosmopolitan creativity the purview of Western artists and non-Western cosmopolitanism a sign of “inauthentic” cultural expression, but this dynamic fosters divergent trends—one, a corporate, commoditized branding of “ethnicity” and corporate authentications of ethnic arts (Comaroff and Comaroff 2009), and two, the burgeoning of African and African diasporic markets in which cosmopolitan creolization is a shared aesthetic of postcolonial experience (Hannerz 1997; Larkin 2008

The process of instrument development for ethnically diverse early adolescents - Anderson, Nancy Lois Ruth; Uman, Gwen C.; Keenan, Colleen; Koniak-Griffin, Deborah; Casey, Conerly (Journal of Early Adolescence, 1996)
Through a combination of pilot study, consultation, and field-testing, an instrument was developed to evaluate the major content areas in the curriculum of a community-based family life education program: parent/child communication, peer influence, family values, self-efficacy, sexuality knowledge, and high-risk behaviors. The wording, format, and question content were structured to be appropriate developmentally for male and female early adolescents 10 through 14 years of age in diverse sociocultural communities in Los Angeles County. Age-related developmental issues facing early adolescents, combined with the ethnic diversity in the county, created serious challenges to the development of a valid, reliable, and relevant instrument for evaluating the effectiveness of an adolescent family life education program. An instrument with some stable and internally consistent components was developed through the key processes of pilottesting and field-testing with focus groups from the target population of ethnically diverse early adolescents.
Created from Fastlane, Scopus look-up